Prevalence of Malaria among Infants and Children with febrile illness: A Hospital Based Study - Ahmad, Shakil; Banu, Farhat; Sharma, Kamal Raj; Thapaliya, Pooja; Subedi, Prativa (Journal of Karnali Academy of Health Sciences, 2020)
Background: About half of the world’s population is at risk of malaria and the burden is particularly high in low-income countries like Nepal. Infants and children are more vulnerable to malaria. Acute febrile illness is the commonest presentation of malaria. Since it is one of the major causes of persistent febrile illnesses in Nepal, empirical antimalarial therapy is usually practiced, especially the endemic areas. A better understanding of the prevalence and clinical profile of malaria helps to tailor the treatment accordingly in cases of undifferentiated febrile illnesses and make the sue of antimalarials more rational. Methods: A cross-sectional observational study was conducted on 200 infants and children presenting with acute febrile illness in the Departments of Pediatrics, Nepalgunj Medical College, from June 2018 to May 2019.Patients were divided in two groups based on the Malarial parasite antigen status. Clinical and laboratory profile of both the groups were compared using Chi square Test. Results: Maximum number of cases in the malaria positive group were of age group 12-15 years. Palor, icterus, hepatomegaly and splenomegaly were significantly more in malaria positive cases (p-value <0.001in all cases) eosinophilia and leucopenia were common in malaria positive cases. Diagnostic accuracy of malaria was found to eb 82 % on combining serology with clinical findings. Conclusion: Prevalence of malaria was found to be more among children than the infants. Although symptoms of malaria are non-specific, clinical findings like pallor, icterus, hepatomegaly and splenomegaly were found to have a significant association with malaria. Combining serology with clinical profile in the prediction of malaria helps promote rational use of antimalarial drugs